Corte Sconta detta Arcana: anatomia di un’incoerenza funzionale. Ovvero come accade che una storia troppo piena di coincidenze per essere davvero credibile sia lo stesso un racconto avvincente e memorabile =Corto Maltese in Siberia: Anatomy of a Functional Incoherence - Daniele Barbieri (H-ermes: Journal of Communication, 2015)
Corto Maltese in Siberia: Anatomy of a Functional Incoherence. A critical reading of CMiS reveals a general weakness in the narrative coherence of the text: too many casual events, playing a crucial role in the development of the story, like if a deus-ex-machina were actually arranging anything. Nonetheless, the reader that approaches CMiS for the first time generally does not feel any sense of artificiality, and even when realizing the weakness of the narrative mechanism the critical reader too can go on and appreciate the quality of Pratt’s work. What, then, does hide or make this weakness scarcely relevant in the general economy of CMiS? This paper argues for looking at Pratt’s text as a sort of (visual) narrative fresco, transforming main narration in just a thin string to collect a sequence of epic and human portraits, each of them suggesting its own semi-mythological narration: and in this the fascination of this text is grounded, much more than in having the protagonist gaining his goal